(untitled) (Research, Society and Development, 2020)
This study aimed to report two cases of bilateral thalamic infarction, one with mesencephalic involvement. The CARE checklist was used to report the two cases. First, (75-year-old) patient with a history of systemic arterial hypertension, had a sudden decrease in the level of consciousness (DLOC), a glasgow coma scale (GCS) 9, tetraparesis, paralysis of the third cranial nerve and left palpebral ptosis, anisocoria, absence of photomotor reflex and divergent strabismus (DS). CT showed hypodensity in the middle mesencephalic region and bilateral paramedian thalamic region. The treatment was conservative, with progress to improve the general condition, but without recovering of cranial nerve paralysis. In the second case, (38-year-old) patient, previously healthy, presented a sudden DLOC, dysarthria and GCS 13. Negative CT, while MRI showed hypersignal in the T2/FLAIR sequences, affecting the paramedian region of both thalamus with a predominance on the right. Conservative treatment was performed, evolving to significant improvement of the neurological condition. Although there is a typical presentation with disorders of mental status and ocular motricity, changes in CT may not be observed, reinforcing the need for attention to the sudden clinic presentation, so that new exams can be performed. It is important, therefore, to report these cases for the rapid diagnosis and appropriate treatment for a better prognosis of the patient.